Wolność, godność i prawo do samostanowienia a udzielanie świadczeń z pomocy społecznej - Sierpowska, Iwona (Wydział Prawa, Administracji i Ekonomii Uniwersytetu Wrocławskiego, 2016)
Freedom and the human right to self-determination are some of key values of social welfare. However, they are not unconditional in nature and may be subject to legal restrictions, which spring from other norms, principles and values that require protection. Dignity is the source of freedom. The need for its protection in connection with such values as life, health and safety may justify helping individuals against their will and, thus, violating their right to self-determination. The provision of social welfare without the individual’s consent requires resolving a moral dilemma and the conflicts between different systems of norms
Keywords: godność; prawo do samostanowienia; opieka społeczna; wolność